Young adulthood across digital platforms : digitally constructing gender and sexualities - Amaral, Inês; Basílio de Simões, Rita; Flores, Ana Marta M. (Emerald Publishing Limited, 2024)
Digital media and mobile-based technologies have changed how young people interact in different spheres of their experiences. Considering the centrality of digital media in young adults' lives, Young Adulthood Across Digital Platforms explores how they engage with mobile applications, incorporating them into their everyday lives and embodying them in their daily practices. Rooted in an intersectional and feminist approach, authors incorporate a future focus on new horizons for researching youth uses of apps and their (re)negotiation of gender and sexual identities from a Media Studies perspective. Adopting a critical lens towards contemporary digital media, chapters consider how young adults navigate digital technologies and mobile applications' technicity and conceptual underpinnings, seamlessly integrating them into their daily routines and utilising them to create engagement between communities that promote health and deconstruct myths of disinformation disorder. As sociocultural products actively reshape gender relations, sexual practices and other core aspects of young people's lives, Young Adulthood Across Digital Platforms posits technology as a potent generator of meaning, subjectivity and agency intricately intertwined with power dynamics.
Includes index.
Keywords: Social media and teenagers.; Feminism.; Social Science -- Sociology -- General.; Social theory.; Sociology.; elektronické knihy; electronic books